2022
DOI: 10.4103/ijn.ijn_88_21
|View full text |Cite
|
Sign up to set email alerts
|

The biological roles of urea: A review of preclinical studies

Abstract: Urea is an organic compound that has been reported to be effective against many pathological conditions. However, many other studies have reported the toxic effects of urea. These controversies on the biological roles of urea remain unresolved. This review aims to evaluate the biological roles of urea in experimental animals from data published in peer-reviewed journals. A PubMed search was conducted using the phrase, “urea application in experimental animals.” A total of 13 publications that met the inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…3, the urea level on day 4 of cesium chloride poisoning was 7.01 ± 0.61 mmol/L, which is 14.3% higher than in the control group. On the 24th day of the study, the blood urea level increased by 31.3% compared to the control value, which may indicate an increase in protein breakdown processes (increased thermogenesis, febrile intoxication syndrome, hepatic decompensation), as well as the development of renal failure as a result of cesium nephrotoxicity (Adeyomoye at al., 2022). The results of the study of creatinine content showed that in the experi-mental group on day 4 of the experiment, its level increased by 1.9 times, and on day 24 by 2.64 times.…”
Section: Discussionmentioning
confidence: 99%
“…3, the urea level on day 4 of cesium chloride poisoning was 7.01 ± 0.61 mmol/L, which is 14.3% higher than in the control group. On the 24th day of the study, the blood urea level increased by 31.3% compared to the control value, which may indicate an increase in protein breakdown processes (increased thermogenesis, febrile intoxication syndrome, hepatic decompensation), as well as the development of renal failure as a result of cesium nephrotoxicity (Adeyomoye at al., 2022). The results of the study of creatinine content showed that in the experi-mental group on day 4 of the experiment, its level increased by 1.9 times, and on day 24 by 2.64 times.…”
Section: Discussionmentioning
confidence: 99%
“…15 The biological activity of urea has not been fully investigated. 15 However, some researchers have proven that urea and thiourea can interact with proteins to inhibit their aggregation. 11,12,16,17 They have specifically demonstrated a chaotropic effect via disintegrating inter-and intramolecular noncovalent interactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several other researchers have been working on the discovery of small molecular scaffolds based on sulfonyls, sulfonamides, , triazoles, thiadiazoles, ureas, , amines, , or aminoindoles, , to impede the formation of oligomers. Urea is a stable hydrophilic functional moiety that is used to convert and store nitrogenous waste in the terrestrial animal body as a metabolic byproduct until excreted . The biological activity of urea has not been fully investigated .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El estudio de la función renal se apoya con el uso de indicadores tales como Nitrógeno Ureico en Sangre (BUN), Urea, Creatinina Sérica (CrS) junto con valores de Tasa de Filtrado Glomerular (TFG), ya que, con el consumo excesivo de proteínas, se genera una producción alta de Urea que se filtra por los riñones y mantiene los niveles sanguíneos entre 12.00 a 54.00 mg/dL. Esto permite monitorear si el aclaramiento de la sustancia es adecuado y no ocurren defectos en el filtrado glomerular que aumenten sus niveles (Adeyomoye et al, 2022). La relación BUN:Creatinina se usa para diferenciar causas de daño renal agudo; a nivel prerrenal por disminución de la perfusión renal o daños intrarrenales incidentes en la nefrona.…”
Section: Introductionunclassified